ETIKA PERILAKU PERIKLANAN DALAM BISNIS ISLAM - Mabarroh Azizah (JESI (Jurnal Ekonomi Syariah Indonesia), 2013)
Abstract If a business wants to develop into large , it is necessary as a means of advertising and promotion for the introduction of memory products to the public . In making the ads required elements are very influential in the success of the advertisement so as to boost sales. Business according to fiqh perspective included in muamalah that allows the human to one another conduct transactions or civil relations . In terms muamalah , any activity is allowed as long as no arguments proscribe ( al - ashlu fil - mu'malah illa al - ibahah ayyadulla dalilun ' ala tahrimiha ) . Trading activities are permissible in Islam as long as there are no elements that conflict with Personality ' such as the element of maysir, gharar and riba. This means that in sharia marketing , the entire process of creating a good process , bidding process , and the process of change in value there should not be things that are contrary to the contract and the principles of Islamic economic . The extent they can be guaranteed and irregularities muamalah Islamic principles does not occur in a transaction or in the form of business processes in the marketing of any transaction can be allowed Keywords: Ethics, Advertising, Islamic business